Personalisation in mass media communication: British online news between public and private - Landert, Daniela (Pragmatics & beyond / New series, 2014)
It seems to be a truism that today's news media present the news in a more personal and direct way than print newspapers some twenty-five years ago. However, it is far from obvious, how this can be described linguistically. This study develops a model that integrates and differentiates between the various facets of personalisation from a linguistic point of view. It includes 1) contexts that involve the audience by inviting direct interaction and through the use of visual elements; 2) the focus on private individuals who are personally affected by news events; and 3) the use of communicative i